Investing in Women : New Evidence for the Business Case - International Finance Corporation (Washington, DC, 2017)
The business case for gender equality is compelling. It is also widely underutilized. The most commonly cited evidence of the business case highlights two points: first, gender equality strengthens national economies, and, second, investing in women in senior leadership strengthens companies in which they work. While both are essential to making the business case, neither represents the full scope of benefits that can be derived from closing gaps between men and women in the private sector. This report supports the business case by highlighting quantitative evidence and best-practice examples from International Finance Corporation’s (IFC) global clients and partners. These cases demonstrate how companies can implement targeted solutions with their employees, entrepreneurs, customers, and community stakeholders. They also illustrate that the business case of studies have sought to highlight the rationale for the private sector to close gaps between men and women. This report offers firm-level data on how companies can benefit from implementing gender-smart solutions. These featured cases represent an array of sectors and geographies. They also offer proof that individual firms can innovate, grow, and profit by closing gender gaps. Finally, the cases demonstrate not just results but a variety of practical approaches for putting the business case into action.